IMPROVEMENT OF KNOWLEDGE OF STUDENTS OF ELEMENTARY SCHOOL OF RANGKAH KIDUL ON HAND WASH THROUGH HEALTH PROMOTION - Elok Triestuning; Rian Prasetyo; Diaz Nur Aindah; Regita Indira Ardianti; Dita Wardatul Anifa; Nurul Khalifah; Dyah Fitri Anggraheni; Dini Fridasari; Sekar Mega Oktavina (Community Service Journal of Indonesia, 2019)
Health Promotion Activities with the title Clean and Healthy Lifestyle with Hand Washing at SDN Rangkah Kidul Sidoarjo Sidoarjo District Sidoarjo Regency is one form of community service in the form of counseling aimed at growing and improving healthy behavior in children from an early age, especially in PHBS Hand Washing. The implementation of these activities on November 15, 2018 took place at Elementary School of Rangkah Kidul, Sidoarjo District, Sidoarjo Regency. The target is students of Elementary School of Rangkah Kidul, Sidoarjo District, Sidoarjo Regency. Before the activity is carried out, there is a process of compiling the activity for 3 weeks before the activity is carried out, starting from the selection of health counseling materials to the submission of licensing to the relevant parties. As an evaluation, the activity was attended by 50 students and 2 teachers, participants participated in the activity with enthusiasm and conducive, the activity can be carried out on time smoothly. Keywords: Hand washing, health promotion, elementary school, counseling.